2020
DOI: 10.1111/bjet.13003
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a marketing virtual reality learning simulation: A quantitative survey with psychophysiological measures

Abstract: Virtual reality (VR) technology has been shown to be a promising teaching method in STEM subjects. Extending these findings, the current study is the first to develop and examine the feasibility of using a VR simulation in marketing (ie, a non‐STEM subject). Specifically, the levels of immersion and three learning outcomes (learning attitude, enjoyment and performance) were compared between the marketing students who learned the same content through a VR simulation prototype versus a traditional static video p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Through the Metaverse, it is possible to see the educational effects that are considered while analyzing and experiencing radioactivity technically and scientifically in Metaverse [220]. Sung et al [221] compared the level of immersion and three learning outcomes (learning attitude, enjoyment, and performance) based on facial electromyography by comparing marketing students with existing static video presentations and showed that the meta world method is effective in education.…”
Section: ) Educationmentioning
confidence: 99%
“…Through the Metaverse, it is possible to see the educational effects that are considered while analyzing and experiencing radioactivity technically and scientifically in Metaverse [220]. Sung et al [221] compared the level of immersion and three learning outcomes (learning attitude, enjoyment, and performance) based on facial electromyography by comparing marketing students with existing static video presentations and showed that the meta world method is effective in education.…”
Section: ) Educationmentioning
confidence: 99%
“…With the continuous progress of laser measurement technology, the speed of laser 3D scanning modeling is getting faster and faster, the accuracy is getting higher and higher, and the operation process is getting easier and simpler. It is one of the most commonly used 3D modeling methods for 3D printing enthusiasts [12]. In order to meet the lightweight requirements of interactive 3D modeling in the Web environment, the hand-drawn sketch data and point cloud data reduction algorithms in the Web environment are designed, respectively [13].…”
Section: Related Workmentioning
confidence: 99%
“…Some studies show that while VR positively influences the attitude towards learning, better results in the area of knowledge are achieved by those using video materials (Sung et al, 2021). Corresponding results have been produced by other studies, where learning with the use of simulation in VR conditions and the conditions of live simulations were compared.…”
Section: Discussionmentioning
confidence: 68%